2020
DOI: 10.1101/2020.07.30.193524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cone-shaped HIV-1 capsids are transported through intact nuclear pores

Abstract: Human immunodeficiency virus (HIV-1) remains a major health threat. Viral capsid uncoating and nuclear import of the viral genome are critical for productive infection. The size of the HIV-1 capsid is generally believed to exceed the diameter of the nuclear pore complex (NPC), indicating that capsid uncoating has to occur prior to nuclear import. Here, we combined correlative light and electron microscopy with subtomogram averaging to capture the structural status of reverse transcription-competent HIV-1 compl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 96 publications
8
56
0
2
Order By: Relevance
“…Using CLEMtomography of IN-positive and eGFP.OR3-negative nuclear complexes, we observed morphologically intact cone-shaped structures with internal density representing the nucleoprotein complex, which closely resembled HIV-1 capsids inside the cytosol or in complete virions. This finding is consistent with our recent study showing that the nuclear pore channel is sufficiently large to accommodate the HIV-1 core and apparently intact cone-shaped HIV-1 capsids can enter the nucleus through intact nuclear pores (Zila et al, 2020). Taken together, these results indicate that reverse transcription initiates in the cytoplasm inside a complete or largely complete capsid, and this capsid-encased complex trafficks into the nucleus, where reverse transcription is completed; subsequently it must be uncoated for integration to occur.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Using CLEMtomography of IN-positive and eGFP.OR3-negative nuclear complexes, we observed morphologically intact cone-shaped structures with internal density representing the nucleoprotein complex, which closely resembled HIV-1 capsids inside the cytosol or in complete virions. This finding is consistent with our recent study showing that the nuclear pore channel is sufficiently large to accommodate the HIV-1 core and apparently intact cone-shaped HIV-1 capsids can enter the nucleus through intact nuclear pores (Zila et al, 2020). Taken together, these results indicate that reverse transcription initiates in the cytoplasm inside a complete or largely complete capsid, and this capsid-encased complex trafficks into the nucleus, where reverse transcription is completed; subsequently it must be uncoated for integration to occur.…”
Section: Discussionsupporting
confidence: 93%
“…CLEM sample preparation equipped with a robotic solution handler (FSP, Leica). FS and embedding into Lowicryl resin was performed according to Kukulski et al (Kukulski et al, 2011) with modifications (Zila et al, 2020).…”
Section: Quantification Of Viral Rna Transcriptsmentioning
confidence: 99%
“…While chromatin-binding is essential for LEDGF/p75’s role in HIV-1 integration ( 127 , 165 ), it is less clear if CPSF6 directly tethers PICs to chromatin for integration. Recent research that indicates the PIC retains its CA complement post-nuclear import ( 62 , 69 , 70 ) is consistent with a model whereby CPSF6 remains PIC-associated post nuclear entry to deliver it to nuclear speckles for integration into SPADs ( 18 ) (Figure 1 ).…”
Section: Introductionsupporting
confidence: 80%
“…The shedding of CA from the core/RTC defines the process of uncoating. Though initially thought to occur soon after virus entry [see ( 68 ) for a review], recent evidence suggests that the PIC structurally resembles the intact or nearly intact core during nuclear import ( 62 , 69 , 70 ). Uncoating ( 62 , 69 ) and the termination of reverse transcription ( 18 , 62 , 69 , 71 , 72 ) are accordingly now thought to occur after nuclear entry.…”
Section: Introductionmentioning
confidence: 99%
“…Though initially thought to occur soon after HIV-1 entry into the cell (see ref. [ 70 ] for discussion), advances in imaging technologies have indicated that intact or nearly intact cores are proficient for nuclear translocation, indicating that uncoating may in large part be a nuclear event [ 71 , 72 , 73 ]. Other CA-binding host factors that have been shown to effect HIV-1 uncoating include cyclophilin A (CypA) [ 74 ], TRIM11 [ 75 ], transportin 1 (TNPO1) [ 76 ], and death domain-associated protein 6 [ 77 ].…”
Section: The Trip To the Nucleusmentioning
confidence: 99%